The Spectrum of Congenital Heart Disease with Transposition of the Great Arteries from the Cardiac Registry of the University of Padua - Frescura, Carla; Thiene, Gaetano (Frontiers in Pediatrics, 2016)
Transposition of the great arteries (TGA) is a cardiac condition in which the arterial trunks arise from the inappropriate ventricle: the aorta from the right ventricle and the pulmonary trunk from the left ventricle [discordant ventriculo-arterial (VA) connection]. In complete TGA the discordant VA connection is associated with situs solitus or inversus and concordant atrioventricular (AV) connection. The hemodynamic consequence of these combined connections is that systemic and pulmonary circulations function in “parallel” rather than in “series”. The presence of situs solitus or inversus associated with both AV and VA discordant connections characterizes a different anatomical complex known as “corrected TGA”. In these hearts, the double discordance at AV and VA level permits a normal sequence of the blood flow from the right atrium to the pulmonary artery and from the left atrium to the aorta. The systemic and pulmonary circulation in these hearts functions regularly in series and the blood sequence is “physiologically corrected”. Thus the term transposition, either complete or corrected, identifies two precise, different anatomical complexes, both characterized by VA discordance. However among congenital heart disease (CHD), there are other anatomical complexes with discordant VA connection in the setting of isomeric atrial situs (right or left) or of univentricular AV connections (double inlet or absent connections). In these latter conditions, the term “transposition” is still necessary to stress that the great arteries are “transposed” in relation to the ventricular septum (aorta from the right ventricle and pulmonary trunk from the left ventricle) but certainly does not figure out the anatomical complexes named complete or corrected transposition. We reviewed the hearts with discordant VA connection of our Anatomical Collection, consisting of 1640 specimens with CHD, with the aim to discuss the anatomy and the frequency of the anatomical variants of TGA and to clarify terminology and classification. The knowledge of the precise anatomy of these malformations results really important for clinical diagnosis and surgical planning.